P172 Association between short-chain fatty acids producing bacteria and CD4 T cells recovery in HIV positive patients. (14th July 2019) - Briseño, Mariana Ruiz; Ratkovich-Gonzalez, Sarah; Alvarez-Zavala, Monserrat; Magaña, Alejandra Vega; Gonzalez-Hernandez, Luz; Solano, Moises Ramos; Andrade-Villanueva, Jaime
Abstract : Background: Antiretroviral Therapy (ART) inhibits HIV replication, allowing immune reconstitution; however, some patients have an insufficient reconstitution, resulting in high levels of immune activation, microbial translocation, inflammation and intestinal dysbiosis. Since microbiota and its metabolites, such as Short-Chain Fatty Acids (SCFA) are linked to immune status, alteration of one or both could be related to poor T cells reconstitution. Methods: HIV+ patients with ART, grouped as immunologic responders, IRs: >350 cells (n= 18), immunologic non-responders, INRs: <350 cells (n= 17) and, healthy controls (n= 14) were recruited. Absolute quantification of Firmicutes, Bacteroidetes, Actinobacteria, Proteobacteria, Bifidobacterium, Clostridium leptum, Clostridium coccoides, Lactobacillus and Faecalibacterium prausnitzii were measured in stool by qPCR. Levels of butyrate, propionate and acetate were quantified in stool by HPLC. Absolute CD4 nadir count, CD4/CD8 proportion and co-expression of HLA-DR/CD38 were determined by flow cytometry. Comparisons between groups were performed with Kruskal-Wallis test. Results: No differences were found in the four main phyla. Regarding probiotics, there were no differences in Lactobacillus and C. coccoides ; however, IRs have less copies of C. leptum and F. prausnitzii in comparison to the other groups. In contrast, INRs presented similar amounts of probiotics as the healthy subjects. No differences were found in SCFA levels, except for acetate which was increased in IRs. Concerning the immune status, there was no difference in CD4 nadir; however, IRs had greater variation in this count and, significantly higher CD4/CD8 proportion. Whereas, co-expression of CD4+HLA-DR+CD38+ was decreased in INRs in comparison with IRs. Conclusion: Immune status from HIV+ subjects directly affects microbiota composition, systemic activation and inflammation. The enrichment of some probiotics, particularly SCFA-producing bacteria, is related to deficient immune reconstitution; however, other gut bacteria could be compensating this decrease. Further studies are necessary to understand how the microbiota and their metabolic products are related to CD4 T cells recovery. Disclosure: No significant relationships.